ANALYSIS OF IMMUNOEXPRESSION OF ESTROGEN RECEPTOR BETA AND EXTRACELLULAR MATRIX METALLOPROTEINASE INDUCER (EMMPRIN) ON TESTICULAR SEMINOMAS NONRECURRENCE AND RECURRENCE - Ridwan, Antonius Janes; Suryanti, Sri; Hassan, Abdul Hadi; Hernowo, Bethy S (Journal of Medicine and Health, 2015)
The most common malignancy of testis is seminoma with prognosis that is not always good because of high recurrence rate and death cases. Extracellular matrix metalloproteinase inducer (EMMPRIN) is a glycoprotein adhesion molecules which plays a role in tumor cell invasion and metastasis as evidenced by immunohistochemistry method in several types of tumor cells and tissue that shows the correlation to the clinical progessivity.This study was conducted by observational descriptive analytics with each seven cases of seminoma nonrecurrences and recurrences diagnosed histopathologically from Dr.Hasan Sadikin Hospital, Advent Hospital and St.Borromeus Hospital in Bandung. This study shows that immunoexpression of estrogen receptor beta is not higher in testicular seminoma recurrence compared with nonreccurence. There was no higher imunoexpression of EMMPRIN receptor on testicular seminoma recurrence compared with nonrecurrence; besides, there was no relationship between immunoexspression of estrogen receptor beta and EMMPRIN in testicular seminoma nonrecurrence and recurrence.In conclusion, immunoexpression estrogen receptor beta expressed in all testicular seminoma, so that the patient could be given an alternative therapy and immunoexspression EMMPRIN, cannot be used to predict a recurrence in patients with seminoma who has received complete therapy.                                                        Keywords: EMMPRIN, Estrogen Receptor Beta, Seminoma Testis nonrecurrence and recurrence